Pembingkaian Media Terhadap Orang Dengan Gangguan Jiwa (ODGJ) dalam Pemberitaan di detik.com - Surya Mutumanikam, Gempita; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
People with mental disorders have not been a mainstream issue in news articles. Throughout January – March 2019, detik.com reported as much as 93 news articles regarding people with mental disorders issue. Based on high quantity of news article release, this issue is perceived as one important issue for detik.com. Therefore, it is important to examine the quality of news article regarding people with mental disorders issue, in order to recognize the concern of detik.com toward this issue. This research aims to examine the frame being used in detik.com news articles of people with mental disorders. Research data sources obtained from random draw of 10 news articles during January – March 2019 period. This research will apply Zhongdang Pan and M. Kosicki’s framing analysis model to look deeper on four aspects of examination consist of syntactical, script, thematic, and rethorical structures. The results indicate, syntactical structure analysis show headline’s picks have a negative tendency, and the sources of news is dominated by people who come from non-psychiatrist background to explain and identify about news subject’ mental condition. In script structure analysis, detik.com emphasizes how from 5W+1H elements related to chronology of incident. Thematic structure analysis indicates three news themes consist of people with mental disorders and criminality, the behavior of people with mental disorders, and people with mental disorders’ rights as citizen. Each theme points out coherency between sentences about mental disorders and criminality, or details about their behavior. In rhetorical structure analysis, the word of perpetrators and victim is used to identify people with mental disorders as criminals, also diction used in detik.com news articles emphasize the behavior of people with mental disorders is inhumane, unsettling, unpredictable, and they have no ability to decide. Photos related to the crime scene or the subject themselves are also used to emphasize the facts regarding the incident. Furthermore, detik.com frame people with mental disorders same as insane. This frame conducted by detik.com indicates, they only viewed this issue as a news value, and reinforce the definition of people with mental disorders as it has been known by society.